Assistência social e o vínculo suas: trânsito da subsidiariedade para o reconhecimento público dos serviços socioassistenciais - Gonçalves, Ana Paula (2016)
This study analyses the social assistance policy on its relationship with civil society organizations in the logic of the Unified System of Social Assistance (SUAS). The construction of new pillars for welfare policy in the country requires the effort of clarifying the strategic and relevant role of civil society organizations and, from these, the social assistance in the provision of social assistance benefits. From this evidence, it is necessary to consider not only their contributions but also their effective participation in building and consolidating the SUAS, especially regarding assurance of the public nature of social assistance services seeking to construct a public sphere of this policy management. With this assumption, it is argued that there is a transition to be established towards organization and development of social assistance services as a public policy, resulting in transformations ranging from the notion of such services to effective measures of the public power in order to bring to light the social needs and the reach and social impact of these benefits. The study is supported by a theoretical, historical and critical methodological axis, from the reading of national data produced by the National Social Assistance Secretariat, through the SUAS’ Census and descriptive analysis of the Electronic Form of Welfare Private Entities and services, programmes, projects and social assistance benefits. Reflections focus on the membership levels established by SUAS, whose upper level of relationship is given by the called SUAS Bond as an enabling process, focused on quality of service and the relationship that is established, therefore, with its providers